Forest management in southern China generates short term extensive carbon sequestration - Xiaowei Tong (Nature Portfolio, 2020)
Forest management may play an important role in climate change mitigation. Here, Tong et al. combine remote sensing and machine learning modelling to map forest cover dynamics in southern China during 2002–2017, showing effects on carbon sequestration that are extensive but of uncertain longevity and possible negative impact on soil water.